An introduction to aircraft structural analysis - Megson, T. H. G. (Butterworth-Heinemann/Elsevier, 2010)
Based on the author's best-selling text Aircraft Structures for Engineering Students, this brief book covers the basics of structural analysis as applied to aircraft structures. Coverage of elasticity, energy methods and virtual work set the stage for discussions of airworthiness/airframe loads and stress analysis of aircraft components. Numerous worked examples, illustrations, and sample problems show how to apply the concepts to realistic situations. Self-contained, this value-priced book is an excellent resource for anyone learning the subject. Covers the core concepts in about 200 fewer pages by removing some optional topics like structural vibrations and aero elasticity Systematic step by step procedures in the worked examples Self-contained, with complete derivations for key equations Based on the author's best-selling text Aircraft Structures for Engineering Students, this Intro version covers the core concepts in about 200 fewer pages by removing some optional topics like structural vibrations and aeroelasticity Systematic step by step procedures in the worked examples Self-contained, with complete derivations for key equations.